Childhood Obesity in Urban Libya: Insights from Primary Schools in Janzour - Mohammed Alaroussi,; Atia, Ahmed; Yosra Sherif, (AlQalam Journal of Medical and Applied Sciences, 2025)
Childhood obesity has emerged as a major public health challenge worldwide, with increasing prevalence in both high-income and low- and middle-income countries. North Africa and the Middle East are experiencing a notable rise in childhood overweight and obesity, reflecting global trends. This study aimed to assess the prevalence of overweight and obesity among primary school children in Janzour, Tripoli, and to explore associations with gender, family history, and lifestyle behaviors. A cross-sectional study was conducted from 25 October to 5 November 2025 in six primary schools across Janzour. A total of 392 apparently healthy children aged 9–18 years were included. Anthropometric measurements were taken by trained intern doctors, and BMI was calculated using the WHO criteria. Questionnaires were administered to collect information on physical activity, dietary habits, and family history of obesity. Data were analyzed using Microsoft Excel, with independent samples t-tests applied to assess gender differences. Of the 392 children, 204 (52%) were boys, and 188 (48%) were girls, with a mean age of 9.18 years. The majority (46.4%) were within the normal BMI range, while 33.2% were underweight, 13.3% overweight, 4.1% obese, and 3.1% severely obese. Gender differences were observed, with underweight and severe obesity more common among males, while females were slightly more represented in the normal weight and obesity categories. Family history of obesity was reported by 26.9% of participants, and within this group, 18.8% were overweight and 14.3% obese. Lifestyle analysis revealed that overweight children often had either healthy diets without physical activity or partial diets with physical activity, whereas obese children exhibited both poor dietary habits and lack of physical activity. Childhood overweight and obesity are emerging concerns in Janzour, reflecting global and regional trends. The findings highlight the combined influence of family predisposition, unhealthy eating patterns, and insufficient physical activity. Early, multi-level interventions involving schools, families, and communities are essential to prevent progression into obesity and reduce future health burdens.